What are you solving for, x or t?
2007-03-22 03:56:42
·
answer #1
·
answered by daisy 5
·
0⤊
0⤋
Solution
2x - 12 - 3t = 60
3x - 12 - 3t + 12 = 60 + 12
4x - 3t = 72
Let x = 0
4x - 3t = 72
4(0) - 3t = 72
- 3t = 72
- 3t / - 3 = 72 / - 3
t = - 24
- - - - - - -
Let
t = 0
2x - 3t = 72
2x - 3(0) = 72
2x - 0 = 72
2x = 72
2x / 2 = 72 / 2
x = 72 / 2
x = 36
- - - - - - - - - -
When
x = 0
t = - 24
When
t = 0
x = 36
- - - - - - - - - -s-
2007-03-22 11:46:04
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
It is impossible to find a solution, in fact the solution implies that one variable is dependent on the other;
2x=72+3t;
x=36+3t/2
2007-03-22 10:58:09
·
answer #3
·
answered by lastdemocratalive 2
·
0⤊
0⤋
which variable do you want to solve for?
x = 3t/2 + 36
t = 2x/3 - 24
2007-03-22 10:57:38
·
answer #4
·
answered by Dave 6
·
0⤊
0⤋
With the information provided, you can only solve for x in terms of t, or t in terms of x. You have two unkowns. If you want a numeric solution for both, you need to have two equations.
2007-03-22 10:59:06
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
2x -12 - 60 = 3t
2x - 72 = 3t
2x - 12 - (2x - 72) = 60
2x - 12 - 2x + 72 = 60
2x -2x = 60 + 12 - 72
0 = 0
2007-03-22 10:59:20
·
answer #6
·
answered by n_d_metcalf 2
·
0⤊
2⤋